1992
DOI: 10.1007/bf00713364
|View full text |Cite
|
Sign up to set email alerts
|

Electric organ polyamines and their effects on the acetylcholine receptor

Abstract: 1. The electric organ of Torpedo nobiliana contained putrescine (PUT), spermidine (SPD), spermine (SPM), and cadaverine (CAD). Traces of acetylated SPD and SPM were occasionaly seen. 2. Upon fractionation of the tissue by differential centrifugation, the polyamines (PA) were found predominantly in the soluble fraction. The postsynaptic membrane fraction, containing a high concentration of acetylcholine receptor (AChR), was proportionally enriched in SPM. The molar ratio of SPM to AChR was approximately two in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Polyamines 1/1 by weight) for primary dog myoblasts using pTG11033 coding for were also shown to bind to and modulate the nicotinic firefly luciferase. Transfections were performed at charge ratio 1, acetylcholine receptor (28,29). Both acetylcholine and which was optimal for both transfection agents (8.5 and 20.4 mg/ml NMDA receptors are present on skeletal muscle fiber total lipid at 10 mg/ml DNA for spermidine-cholesterol / DOPE and Lipofectin, respectively).…”
Section: Fig 4-continuedmentioning
confidence: 99%
“…Polyamines 1/1 by weight) for primary dog myoblasts using pTG11033 coding for were also shown to bind to and modulate the nicotinic firefly luciferase. Transfections were performed at charge ratio 1, acetylcholine receptor (28,29). Both acetylcholine and which was optimal for both transfection agents (8.5 and 20.4 mg/ml NMDA receptors are present on skeletal muscle fiber total lipid at 10 mg/ml DNA for spermidine-cholesterol / DOPE and Lipofectin, respectively).…”
Section: Fig 4-continuedmentioning
confidence: 99%
“…Preparation of Torpedo californica Electroplax Membrane and Determination of AChR Concentration. The method of preparation was modified from the methods described by Szczwinska et al (52). Frozen T. californica electric organs were purchased from Pacific Bio-Marine (Venice, CA).…”
mentioning
confidence: 99%
“…Szczawinska et al [116] likewise found that at concentrations above 1 mM, spermine inhibited ion influx and α-bungarotoxin binding to Torpedo electric organ nAChRs, thereby acting as a competitive antagonist of the nAChR. In contrast, at sub-µM concentrations, spermine enhanced cation influx by about 20%, effectively acting as an nAChR agonist.…”
Section: Resultsmentioning
confidence: 99%